1995
DOI: 10.1055/s-0038-1653820
|View full text |Cite
|
Sign up to set email alerts
|

Arg506GIn Factor V Mutation (Factor V Leiden) in Patients with Ischaemic Cerebrovascular Disease and Survivors of Myocardial Infarction

Abstract: SummaryThe point mutation Arg506->Gln of factor V was recently shown to be an important and relatively common genetic cause of venous thromboembolism. Using a DNA technique based on polymerase chain reaction, we surveyed the blood samples of 236 patients with ischaemic stroke or a transient ischaemic attack, 122 survivors of myocardial infarction and 137 control subjects for the presence of this mutation. Although the frequency of the factor V mutation in patients with arterial disease (4.5%) was not signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
5
2

Year Published

1998
1998
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(79 citation statements)
references
References 11 publications
4
68
5
2
Order By: Relevance
“…We concluded that platelet hyperaggregation may be considered to be a more specific marker of migraine. Conflicting results have been reported regarding the prevalence of genetic prothrombotic risk factors in migraine [18][19][20][21][22][23]. In our study, in accordance with Corral et al [20] and Soriani et al [22], the frequencies of the two main prothrombotic polymorphisms for venous thromboembolism (Leiden, prothrombin) did not differ from those of controls.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…We concluded that platelet hyperaggregation may be considered to be a more specific marker of migraine. Conflicting results have been reported regarding the prevalence of genetic prothrombotic risk factors in migraine [18][19][20][21][22][23]. In our study, in accordance with Corral et al [20] and Soriani et al [22], the frequencies of the two main prothrombotic polymorphisms for venous thromboembolism (Leiden, prothrombin) did not differ from those of controls.…”
Section: Discussionsupporting
confidence: 89%
“…A Finish study detected a higher frequency of migraine with aura in patients suffering from ischemic stroke who carried the factor V Leiden (67%) than in those who had no mutation (26%) [18]; these findings were subsequently confirmed by Leone et al [19]. In contrast, a case-control study did not find a significantly higher frequency of several prothrombotic factors (factor V Leiden, G20210A mutation of factor II, decanucleotide insertion/deletion in factor VII promoter, HPA-1 and HPA-2 polymorphisms) in 106 migrainous patients compared to healthy controls [20], even if a particularly high frequency of factor V Leiden, not reaching statistical significance, was found in patients suffering from migraine with aura.…”
mentioning
confidence: 99%
“…Our data agree with these observations since this lower incidence may partly reflect the absence of the most important known cause of venous thrombophilia (the FVL mutation) in this ethnic group. The possibility that FVL might be a genetic risk factor for arterial thrombotic disease has been investigated in several studies, but with conflicting results (Prohaska et al, 1995;Kontula et al, 1995;van der Bom et al, 1996;Foley et al, 1997). However, a recent study demonstrated a clear relationship between the presence of FVL and increased predisposition for myocardial infarction in young women (Rosendaal et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Worth noting is that the only other published study tackling the genetic aspects of juvenile migraine has, based on evidence suggestive of an association between migraine and prothrombotic genetic risk factors, considered the factor V Leiden mutation [15] due to its high prevalence in patients with stroke and history of migraine [16]. As in our experience, no difference in the prevalence of this mutation was found in children and adolescents with migraine with aura vs. controls.…”
Section: Molecular Studies Of the Genetic Factors In Adult Migrainementioning
confidence: 42%